Too low to be true: The use of minimum thresholds to fight tax evasion - Mirco Tonin (Institute for the Study of Labor (IZA), 2011)
The enforcement of compliance with tax regulation is a complex task. This is particularly the case when the administrative capacity of the tax authority is low, as it often happens in developing and transition countries. This paper draws on some international experiences in fighting tax evasion to identify tools that can be used to reduce underreporting by employed labor, small and medium enterprises, self-employed, and professionals. In particular, I analyze the use of minimum thresholds, where taxpayers cannot declare an income below a certain amount or, alternatively, are subject to a higher probability of an audit if they decide to do so. First, I model the impact of minimum thresholds by explicitly taking into account low administrative capacity. The model shows that introducing a threshold creates a spike and a missing middle in the distribution of declared incomes and highlights under which conditions a threshold is likely to increase net revenues. I then analyze two policies used to fight underreporting: the Italian Business Sector Analysis and the Bulgarian Minimum Social Insurance Thresholds. The Italian tax authority infers normal revenues and compensations by small and medium enterprises, self-employed, and professionals from indicators that are difficult to conceal or manipulate. In case the taxpayer decides to declare less than the normal level, the probability of an audit increases and the burden of proof is reversed. Bulgaria has established a system of differentiated minimum social insurance thresholds depending on sector and profession, so that social security contributions cannot be lower than the ones implied by the threshold. To conclude, I appraise the applicability of these two systems in other countries.
urn:nbn:de:101:1-201104113827
Keywords: H26; K35; K42; P37; 330; tax evasion; minimum threshold; studi di settore; Steuervermeidung; Steuerpolitik; Steuertarif; Theorie